The Concept of Al-Barzakh in the Thought of Muḥyiddīn Ibn ʿArabī: A Philosophical and Mystical Analysis - Assadi , Jamal; Na'amneh, Mohammed; Sindawi, Khalid (Journal of Posthumanism, 2025)
This study explores the concept of al-Barzakh in the thought of Muḥyiddīn Ibn ʿArabī (d. 1240), arguing that Barzakh is not merely an eschatological waiting period but a fundamental ontological principle that governs the relationship between opposites—existence and non-existence, seen and unseen, finite and infinite. Through a detailed analysis of Ibn ʿArabī’s metaphysical system, the paper examines how Al-Barzakh functions as a bridge between realms, particularly between the physical world (ʿālam al-shahāda), the unseen world (ʿālam al-ghayb), and the imaginal realm (ʿālam al-mithāl). The study further explores the epistemological and linguistic dimensions of Al-Barzakh, revealing its role as an intermediary in human perception and language. Ibn ʿArabī’s insights anticipate modern poststructuralist theories, particularly Derrida’s différance, by highlighting how language remains forever suspended between revealing and concealing meaning. This research situates Ibn ʿArabī’s cosmological and linguistic Barzakh within a broader comparative framework, engaging with Neoplatonic, Taoist, and contemporary philosophical thought. Ultimately, it demonstrates that Al-Barzakh is not only a concept within Islamic eschatology but a dynamic and universal structure of existence, perception, and knowledge.